2019
DOI: 10.1128/microbiolspec.psib-0003-2018
|View full text |Cite
|
Sign up to set email alerts
|

Type I Secretion Systems—One Mechanism for All?

Abstract: Type I secretion systems (T1SS) are widespread in Gram-negative bacteria, especially in pathogenic bacteria, and they secrete adhesins, iron-scavenger proteins, lipases, proteases, or pore-forming toxins in the unfolded state in one step across two membranes without any periplasmic intermediate into the extracellular space. The substrates of T1SS are in general characterized by a C-terminal secretion sequence and nonapeptide repeats, so-called GG repeats, located N terminal to the secretion sequence. These GG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…The T1SS is well characterized in many extracellular bacteria and is known to secrete a number repeat-containing pore-forming toxins known as the Repeats in Toxin Family (RTX) (70,71). The T1SS is widespread in Gram-negative bacteria and transports substrates in a one-step process across two membranes without any periplasmic intermediate into the extracellular space (72)(73)(74)(75). Several T1SS substrates have been identified that are secreted by members of Anaplasmataceae, including ankyrin repeat (AR) and tandem repeat effector proteins.…”
Section: Secretion Systems and Effectorsmentioning
confidence: 99%
“…The T1SS is well characterized in many extracellular bacteria and is known to secrete a number repeat-containing pore-forming toxins known as the Repeats in Toxin Family (RTX) (70,71). The T1SS is widespread in Gram-negative bacteria and transports substrates in a one-step process across two membranes without any periplasmic intermediate into the extracellular space (72)(73)(74)(75). Several T1SS substrates have been identified that are secreted by members of Anaplasmataceae, including ankyrin repeat (AR) and tandem repeat effector proteins.…”
Section: Secretion Systems and Effectorsmentioning
confidence: 99%
“…(iv) The type I secretion system HlyBD-TolC in E. coli contains the MsbA and LmrA homologue HlyB as the ABC translocator [72]. The extrusion of the secretion competent Cterminal peptide (Actp) of the toxin protein haemolysin A by HlyBD-TolC was reported to be severely inhibited by the proton ionophore carbonylcyanide m-chlorophenylhydrazone (CCCP), which collapses simultaneously the Δy and ΔpH.…”
Section: Importance Of Nbds In Transport Efficiencymentioning
confidence: 99%
“…Functional diversity is present as well: While many members of this family are cytolytic toxins, e.g., Escherichia coli hemolysin HlyA or Bordetella pertussis adenylate cyclase CyaA, other members are the nodulation-signaling protein NodO protein from Rhizobacterium leguminosarum, or possess hydrolytic activity, e.g., proteases such as the serralysins from Pseudomonas aeruginosa or lipases like LipA from Serratia marcescens (reviewed in [5]). A common denominator of probably all of these proteins is the secretion by a type I secretion system (T1SS), which requires a C-terminal non-cleavable signal sequence that is generally preceded by a variable number of nonapeptide tandem repeats [6,7,8,9,10]. These repeats coined the denotation of the RTX toxins [3].…”
Section: Introductionmentioning
confidence: 99%